2005
DOI: 10.1128/iai.73.12.7988-7995.2005
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal and Maternal Immunological Responses to Conserved Epitopes within the DBL-γ3 Chondroitin Sulfate A-Binding Domain ofPlasmodium falciparumErythrocyte Membrane Protein 1

Abstract: Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) mediates the adherence of P. falciparuminfected erythrocytes to placental syncytiotrophoblasts via interactions with chondroitin sulfate A (CSA), a characteristic of pregnancy-associated malaria. Pregnancy-associated malaria predicts increased susceptibility of newborns to malaria, and it is postulated that transplacental passage of parasite antigen induces immune regulatory activity in the neonate. We wished to examine the immune responsiveness to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
(42 reference statements)
1
15
1
Order By: Relevance
“…These studies have measured cytokine responses of CBMC using ELISPOT (12,24), intracellular staining (13,25,36), or in culture supernatants following stimulation with mitogen, MA extract, MSP1, and RESA (13,15,25). All of the studies concluded that malaria-specific T cell priming occurs in utero.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have measured cytokine responses of CBMC using ELISPOT (12,24), intracellular staining (13,25,36), or in culture supernatants following stimulation with mitogen, MA extract, MSP1, and RESA (13,15,25). All of the studies concluded that malaria-specific T cell priming occurs in utero.…”
Section: Discussionmentioning
confidence: 99%
“…In 1988, Desowitz (1) reported that CBMC from newborns in Papua New Guinea proliferated when cultured with an extract of malarial parasites, whereas babies born in a malaria-free area did not. Subsequently, malaria-specific T cell proliferation and cytokine responses were found in CBMC of newborns in Kenya, Gabon, Togo, and Cameroon (12)(13)(14)(15). Thus, there is substantial evidence for in utero priming of T cells to malaria.…”
mentioning
confidence: 93%
“…The nature of the initial exposure to malaria Ags likely affects the potentially diverse roles assumed by T regs in malaria infection. For some individuals, this first experience appears to occur in utero (10,12,14,17,83,84). This may have an important impact on the subsequent development of an individual's immune response to malaria and potentially to other Ags.…”
Section: Cd25mentioning
confidence: 99%
“…Substantial amounts of IL-10 are produced by CBMC in malariaexposed fetuses (14,15,17,38), which are thought to be important for immunoregulation (36,38,71). This can occur both spontaneously and in response to malaria blood-stage Ags, suggesting that expansion of IL-10-producing T cells may be important for modulating malaria Ag-specific immune responses.…”
Section: Cd25mentioning
confidence: 99%
See 1 more Smart Citation